Tingkat Kesukaan Konsumen Terhadap Serat Kenaf Organik dengan Pewarna Alami - Rusmini, Rusmini; Aquastin, Dwinita; Manullang, Riama Rita; Daryono, Daryono (Jurnal Penelitian Pertanian Terapan, 2019)
Production of kenaf fiber for industry mostly uses chemical fertilizers with synthetic dyes that will also cause health and environmental problems and adversely affect all life forms. Increased health and environmental concern make organic kenaf fiber production with natural dyes highly recommended for both handicrafts and for industrial scale because natural fertilizers and dyes are non-toxic, decomposable, and environmentally friendly. The purpose of this study is to determine the level of consumer preference to organic kenaf fiber with natural dyes. The study used a two-factor group randomized design with the first factor of organic kenaf fiber and a second factor of natural dye consisting of 3 levels. The research was repeated as many as 2 replications so that there were 6 experimental units. Variables observed by consumer's level of craft product from organic kenaf fiber with natural dye covering color, texture and odor tested. This test is done by Hedonic Test method, using questionnaire with untrained panelist (consumer) as many as 40 people with data obtained based on a panelist response using a hedonic scale was analyzed by Kruskal-Wallis test. The results showed that there was no significant difference in consumer preferences for the color, texture and odor of organic kenaf fiber with various natural dyes.